2014
DOI: 10.1111/josi.12060
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Racial Discrimination, Drug Use, and Psychological Distress in African American Youth: A Pathway to Child Health Disparities

Abstract: Experiences of racial discrimination and social inequality are related to higher levels of psychological distress and substance use that may contribute to health disparities among youth. This within-group quantitative survey study tested two alternative theoretical models of the relations between perceived racial discrimination, psychological distress, alcohol, and marijuana use in a sample of 567 African American high school students (61% female; mean age = 15.6 years).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 69 publications
0
29
0
Order By: Relevance
“…African American youth are more likely than their Caucasian counterparts to encounter neighborhood disorder, exposure to community violence, and experiences with racial discrimination [2628]. Moreover, there are barriers in workplaces, schools, and communities that disproportionately affect African Americans and African Americans are more likely to be incarcerated for drug use.…”
Section: Discussionmentioning
confidence: 99%
“…African American youth are more likely than their Caucasian counterparts to encounter neighborhood disorder, exposure to community violence, and experiences with racial discrimination [2628]. Moreover, there are barriers in workplaces, schools, and communities that disproportionately affect African Americans and African Americans are more likely to be incarcerated for drug use.…”
Section: Discussionmentioning
confidence: 99%
“…A study exploring the relationship between racial discrimination and behavioral outcomes among black youth found increased encounters with racial discrimination placed youth at risk for increased participation in delinquency and suicide ideation . Research across several studies reveal young people who report more encounters with racial discrimination are at risk for developing depressive symptoms and other risk‐oriented behaviors . One particular study found experiencing racial discrimination from teachers can lead to feelings of alienation and low levels of motivation .…”
Section: Literature Reviewmentioning
confidence: 99%
“…12,13 Research across several studies reveal young people who report more encounters with racial discrimination are at risk for developing depressive symptoms and other risk-oriented behaviors. 39,41 One particular study found experiencing racial discrimination from teachers can lead to feelings of alienation and low levels of motivation. 42 Research also indicates young people who report more encounters with racial discrimination demonstrate more problem behaviors and use of alcohol and marijuana.…”
Section: Racial Discriminationmentioning
confidence: 99%
“…Various studies have demonstrated that perceived discrimination significantly deteriorates both physical and mental health (Pascoe and Smart Richman, 2009a,b;Williams and Mohammed, 2009;Williams et al, 2003). Experiences of discrimination and racism are associated with psychological distress, anxiety and depression as well as increased alcohol, tobacco and marijuana use among Black Americans (Brown et al, 2000;Landrine and Klonoff, 1996;Sanders-Phillips et al, 2014). Discrimination leads to health disadvantages by elevating physiological stress responses such as blood pressure, cardiovascular reactivity and heart rate (Brondolo et al, 2003;Clark et al, 1999;Clark, 2000Clark, , 2006aHarrell et al, 2003;Mays et al, 2007;Pascoe and Smart Richman, 2009a,b;Williams, 2012).…”
Section: Diversity Well-being and Healthmentioning
confidence: 96%